2018
DOI: 10.1021/acsphotonics.7b01176
|View full text |Cite
|
Sign up to set email alerts
|

Topological Engineering of Interfacial Optical Tamm States for Highly Sensitive Near-Singular-Phase Optical Detection

Abstract: Abstract:We developed planar multilayered photonic-plasmonic structures, which support topologically protected optical states on the interface between metal and dielectric materials, known as optical Tamm states. Coupling of incident light to the Tamm states can result in perfect absorption within one of several narrow frequency bands, which is accompanied by a singular behavior of the phase of electromagnetic field. In the case of near-perfect absorptance, very fast local variation of the phase can still be e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 64 publications
(170 reference statements)
2
90
0
Order By: Relevance
“…The predictions of the reflectance spectra of mesoporous metamaterial samples were done by using the semi-analytical transfer matrix method 59,60 ( Supplementary Fig. S5).…”
Section: Methodsmentioning
confidence: 99%
“…The predictions of the reflectance spectra of mesoporous metamaterial samples were done by using the semi-analytical transfer matrix method 59,60 ( Supplementary Fig. S5).…”
Section: Methodsmentioning
confidence: 99%
“…1b, blue line). The choice of the operational wavelength is arbitrary, and the resonance can be easily tuned across the visible and infrared spectral ranges by adjusting the parameters of the structure (i.e., layer thicknesses or materials) [37]. Unlike surface plasmon polariton modes that are p-polarized, Tamm plasmon modes can be excited by incident waves of both orthogonal s-and p-polarizations [21,22].…”
Section: Tamm Plasmon Properties: Conjugate Impedance Matching Yieldsmentioning
confidence: 99%
“…We have recently demonstrated that perfect Tamm absorbers can be designed by conjugate impedance matching finite-size 1D photonic crystals and metal surfaces [37]. Below their plasma frequency, metal surfaces are characterized by predominantly reactive impedances (i.e., with { } > { }).…”
Section: Tamm Plasmon Properties: Conjugate Impedance Matching Yieldsmentioning
confidence: 99%
See 2 more Smart Citations